The effects of phytoestrogen content of soybean meal on sex reversal of Nile tilapia (Oreochromis Niloticus) fry - El-Sayed, Heba M. A.; El-sayed, Abdel-fattah M.; Abdel-Aziz, Sayeda H. (2010)
Two consecutive experiments were camed out to evaluate the effect of phytoestrogen (genistein and daldzeln) contained in soy bean meal (SBM) on sex reversal of Nile tilapia fry, fed on SSM-based diets treated with 17o-Melhyl Testosterone (MT). In the first experiment, swim up Nile tilapia fry were fed four test diets; fishmeal (FM)-based diet without MT (control), FM-based diet treated with MT (60 mg/kg), SBM diet treated with MT (60 mg/kg) and soybean diet w~hout any hormone treatment, for 2B days. The results indicated that the fish fed on the control FM diet resulted in 1:1 male: female ratio, while fish fed on FM diet treated with MT resulted in 97% males. Untreated SSM diet lead to 77% females, while the fish which were fed with soybean diet treated with MT produced 31% females and 69% males. This result indicated the phyloestrogen contents of SBM may have significant effect on sex reversal of Nile tilapia fry.
1
Keywords: Nile tilapia -- Feeding and feeds; Nile tilapia -- Nutrition; Soybean as feeds; Phytoestrogens -- Physiological effect